Toward a sustainable heartland: contrasting future agricultural scenarios in Kansas - Neufer, Savannah N. (Kansas State University, 2012)
Agriculture is vital to the character of Kansas. It is threaded through the social, economic, and environmental systems that operate in Kansas and bring each system into interaction with one another. Loss of agriculture would mean drastic changes to traditional Kansas way of life due to the three pronged nature of agriculture in Kansas. Continuation of agricultural activity then is of great importance. Globalization, climate change, and environmental change pose threats to agricultural futures. This study is a meta-analysis of current literature in an attempt to assess the current state of sustainable agriculture in the state of Kansas. An emphasis was placed on climate as a driver of change and ways in which agricultural producers in Kansas may begin implementing sustainable adaptations. Barriers to implementing sustainable agricultural adaptations were also identified in the literature. Broadly speaking analysis focused on barriers created through policy and barriers created through gaps in knowledge and weak or missing connections, or cognitive barriers. Information gathered in the course of the literature analysis was used to generate two potential future agricultural scenarios for Kansas. Scenarios can be used to aid policy makers in assessing potential impacts of environmental change and interactions between different systems and scales. Two separate scenarios, Business-As-Usual and Sustainable-Adaptive, were developed with distinct characteristics. The Business-As-Usual scenario represents a future that is framed similar to the current situation. Changes built into the scenario stem from the projected changes to climate. The remainder of the narrative describes a future that has pursued developmental pathways driven by current policy and market forces. In contrast, the Sustainable-Adaptive scenario represents a Policy Reform scenario in which there is strong guidance through policy towards a developmental pathway that focuses on sustainable agricultural methods. This scenario describes a future in which environmental degradation is slowed or even reversed. Continued future work may focus on the role of water availability, community level impacts of sustainable adaptations, and the integration of stakeholder values as another layer of complexity in future scenarios.
Keywords: Adaptation; Agriculture; Kansas; Sustainability; Barriers; Scenarios; Geography (0366); Sustainability (0640)